COMPARISON OF HOMOGENEITY BETWEEN LYOPHILISED CONTROL MATERIAL AND IN-HOUSE CONTROL MATERIAL FOR GLUCOSE EXAMINATION - Aulia Risqi Fatmariza; Angga Eka Kurnia, Danny Meganingdyah Primartati (CV. ADIBA AISHA AMIRA, 2025)
Background: Internal Quality Assurance (IQA) is a continuous monitoring activity by the laboratory to reduce or prevent errors in examination results using control materials. Homogeneity of the control material is very important because homogeneity shows that the control material is the same. Objective: To find out whether there is a difference in homogeneity between the lyophilized control material and the in-house control material for glucose examination. Research method: The type of research used was a quasi experiment with a simple random sampling technique at the SMC Clinical Laboratory, Telogorejo Hospital, Semarang. Data analysis uses the homogeneity calculation formula. Results: Based on the results of homogeneity calculations, it is known that the Fcount for the lyophilized control material is 0.9538 while the in-house control material is 2.1883, where both are <Ftable (3.02) which means homogeneous. Conclusion: There is no difference in homogeneity between lyophilized control material and in-house control material for glucose examination.